Pengaruh Workplace Spirituality terhadap Job Related Affective Well-being pada Guru di SMK Swasta Kota Bandung - Muhammad Fardan Ardiansyah Permana; Hendro Prakoso (UNISBA Press, 2023)
Abstract. This study aims to determine and analyze the effect of Workplace Spirituality which has three aspects, meaningful work, sense of community, and alignment with organizational values on Job Related Affective Well- being on teachers at Vocational High School in Bandung. The research method used is the causality method with the number of subjects as many as 98 teachers at the Bandung City Vocational High School. This study uses a psychological scale with a workplace spirituality measurement tool from Milliman, Gatling, Kim, and a job related affective well-being measurement tool from Van Katwyk, Fox, Spector, & Kelloway. The results of the study found that 94.90% of teachers had high workplace spirituality and 60.20% of teachers had high job-related affective well-being. The results of multiple regressions show that workplace spirituality has an effect of 69.9% on job related affective well-being, while the meaningful work aspect has the largest effect, which is 33.82%, sense of community is 23.88% and the aspect of alignment with organizational values has the smallest effect, which is 12.19%. Abstrak. Penelitian ini bertujuan untuk mengetahui, dan menganalisis pengaruh Workplace Spirituality yang memiliki tiga aspek yaitu meaningful work, sense of community, dan alignment with organizational value terhadap Job Related Affective Well-being pada guru di SMK Swasta Kota Bandung. Metode penelitian yang digunakan adalah metode kausalitas dengan jumlah subjek sebanyak 98 orang guru di SMK Swasta Kota Bandung. Penelitian ini menggunakan skala psikologis dengan alat ukur workplace spirituality dari Milliman, Gatling, Kim, serta alat ukur job related affective well-being dari Van Katwyk, Fox, Spector, & Kelloway. Hasil penelitian ditemukan 94.90% guru memiliki workplace spirituality tinggi dan 60.20% guru memiliki job related affective well-being tinggi. Hasil multiple regression menunjukkan workplace spirituality memiliki pengaruh sebesar 69.9% terhadap job related affective well-being, sedangkan aspek meaningful work memberikan pengaruh paling besar yaitu 33.82%, sense of community sebesar 23.88% dan aspek alignment with organizational value memberikan pengaruh paling kecil yaitu 12.19%.